Fundamentals of Systematic Zoology (University Journal of Zoology, Rajshahi University, 2010)
Title: Fundamentals of Systematic ZoologyAuthor: Md. Ataur Rahman KhanPublisher Zahirul Islam (Lipton), Aligarh Library, Rajshahi.March, 2010, Pp. 380.DOI: 10.3329/ujzru.v28i0.5295Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 83